Literature Review Implementasi Bermain Peran Untuk Perkembangan Kemampuan Sosial Emosional Anak - Ashar Ashar; A. Rezky Nurhidaya; Reski Idamayanti (Departement of Mathematics Education, 2023)
Role-playing for early childhood is fun for students, so role-playing children need to pay attention to the interests and motivations of students. This study aims to analyze the implementation of role playing and describe the impact of emotional social development, this research was conducted using a literature review by collecting reference materials from various articles and journals based on the research objectives. The results of the literature review research related to the implementation of role playing while still requiring a foothold during role playing and paying attention to supporting factors by using the right media, educator creativity, teaching techniques and things that need to be anticipated by students' egocentrism and, undisciplined children and shy students. The impact of role playing obtained is courage, self-confidence, independence and communication as well as social interaction, and role playing has a significant influence on aspects of the development of social emotional skills of early childhood in kindergarten.